Blue Rubber Bleb Nevus Syndrome in the Obstetric Patient: A Case Report of Anesthetic Implications and Management. Issue 8 (23rd August 2021) - Hult, Martin; Halldorsdottir, Halla; Vladic Stjernholm, Ylva; Hein, Anette; Jörnvall, Henrik
Abstract : Supplemental Digital Content is available in the text. Abstract : Blue rubber bleb nevus syndrome (BRBNS) is a rare systemic syndrome characterized by venous malformations usually found in the skin and visceral organs. To date, 11 case reports describing BRBNS during pregnancy have been published. To our knowledge, this is the first report describing intracranial, airway, epidural, and birth canal involvement of venous malformations in the same parturient. Key lessons learned include clinical presentation, workup, team management, and care of obstetric patients with this disorder.